2014
DOI: 10.1590/s2317-64312014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho nas habilidades da linguagem em crianças nascidas prematuras e com baixo peso e fatores associados

Abstract: Purpose: To examine the language development at chronological age 2 to 3 years of children born preterm with low birth weight and its associated risk factors. Methods: In this cross-sectional study, children were assessed using the Denver Developmental Screening Test (Denver II test) and Early Language Milestone Scale (ELM scale). The chi-square test was used and all variables with p<0.20 were entered in a binary logistic regression model; statistical significance was set at p<0.05. Results:Among the 77 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
(44 reference statements)
2
2
0
14
Order By: Relevance
“…These findings corroborate other studies that showed an association between low birth weight, manifested by prematurity, poorer performance in language assessment tests, and delayed language acquisition and development (29) . With regards to Apgar, one study showed that altered values in Apgar were associated with later development of Specific Language Disorders (SLD) in children (30) .…”
Section: Discussionsupporting
confidence: 91%
“…These findings corroborate other studies that showed an association between low birth weight, manifested by prematurity, poorer performance in language assessment tests, and delayed language acquisition and development (29) . With regards to Apgar, one study showed that altered values in Apgar were associated with later development of Specific Language Disorders (SLD) in children (30) .…”
Section: Discussionsupporting
confidence: 91%
“…It was also observed that the children born with lower weight performed worse on the language assessments when compared to the children with higher weight and a gestational age closer to 37 weeks, in line with the findings of studies included in this review 27,28 . During standardized assessment, preterm children have scored lower on intelligence scales, visual perception test, visual-motor integration test, memory and attention, impairments that go beyond the actual The first study was aimed at comparing the neuropsychomotor development of preterm infants (with corrected age) and full-term children between six and 12 months of age, as well as to investigate the associated factors.…”
Section: Discussionsupporting
confidence: 86%
“…No MARGOTTO, 2012;CALDAS et al, 2014;CHATTOPADHYAY;MITRA, 2015;PACHELLI, 2015;IONIO et al, 2016;MELLO et al, 2016;ROGERS;HINTZ, 2016;WONG et al, 2016;MILNER et al, 2017;RIBEIRO et al, 2017). CHATTOPADHYAY; MITRA, 2015;PACHELLI, 2015;IONIO et al, 2016;MELLO et al, 2016;ROGERS;HINTZ, 2016;WONG et al, 2016;MILNER et al, 2017;RIBEIRO et al, 2017) como indicadores de risco substanciais para alteração do desenvolvimento infantil, sobretudo quando associado a outros fatores de risco.…”
Section:  Independent Samples Testunclassified
“…CHATTOPADHYAY; MITRA, 2015;PACHELLI, 2015;IONIO et al, 2016;MELLO et al, 2016;ROGERS;HINTZ, 2016;WONG et al, 2016;MILNER et al, 2017;RIBEIRO et al, 2017) como indicadores de risco substanciais para alteração do desenvolvimento infantil, sobretudo quando associado a outros fatores de risco. Os fatores de risco indicados nos estudos referem-se, além da IG e do peso, o tempo de permanência em UTI, a quantidade de fatores intercorrentes pré-natais (maternos e/ou fetal) peri e pós-natais, a síndrome do desconforto respiratório, a persistência do canal arterial, a nota de Apgar reduzido, dentre outros (RAMOS; CUNAN, 2009;CASKEY;VOHR, 2013;CALDAS et al, 2014;RENZ et al, 2015;ZERBETO;CORTELO;FILHO, 2015;CHATTOPADHYAY;MITRA, 2015;LINSELL et al, 2015;RECHIA et al, 2016;BLAIR;PICKLER;ANDERSON, 2016;ROVER et al, 2016;MILNER et al, 2017). Cabe ressaltar, entretanto, que há uma expectativa de ganho de peso com o desenvolvimento da gestação.…”
Section:  Independent Samples Testunclassified
See 1 more Smart Citation